Complex Analytical Study of the Stability of Tunnel-Surrounding Rock in a Layered Jointed Rock Mass. (16th October 2020) - Wu, Su; Li, Kegang; Yang, Zaihong; Wu, Shunchuan; Wang, Ting; Qin, Qingci; Li, Mingliang
Abstract : A barrier function method based on the fmincon optimization function in MATLAB was used to determine the function to map a tunnel boundary to the unit circle in the complex plane, and a structural failure criterion of the mapping convergence was established based on the reliability theory of underground engineering. The joints were approximated as cracks around the tunnel, the anisotropy of the stress intensity factor due to the crack inclination and position changes was studied, and the modified scoring parameter of the layered joints around the tunnel for the rock geomechanics classification (RMR) was proposed and used at points around the tunnel. The calculation method for the supporting stress was required to balance the bias load. The results showed the following: (1) When taking the structural failure criterion as the convergence condition of the mapping function, the mapping function converged when the mapping accuracy was δ ≥ 31.74 % . (2) The crack with an inclination angle of β = 45 ° was the dominant structural plane of the jointed rock mass around the tunnel. The anisotropy of the stress intensity factor K II at the tip of the mode II crack indicated that the corresponding cracks at the various points around the tunnel had inconsistent influences on the tunnel. The position had the greatest influence, followed by the straight wall area, and then by the top and floor areas. (3) When the crack inclination β was equal to the inclination angle β 0 of the dominant joint plane, the secondary crack was parallel to the unloading surface of the corresponding tunnel. (4) The bias load formed by the layered joints around the tunnel reduced the stress threshold of the failure of the rib spalling.